Does Network Theory Connect to the Rest of Us? A Review of Matthew O. Jackson's Social and Economic Networks - Rauch, James E (Journal of Economic Literature, 2010)
The ubiquity of networks in our social lives has long been recognized, and their importance in our economic lives is increasingly recognized as well. Yet the literature synthesized in Matthew O. Jackson's Social and Economic Networks, which covers the theory of how networks form, decay, and shape behavior at a general level, has had little influence on either applied theory or empirical work in this area. This is partly because of limitations of network theory as it has evolved in this literature. After describing the network theory presented in the book, I discuss these limitations and make some tentative suggestions as to how they might be overcome. (JEL D85, L14, Z13)